(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2022)
The aim of this article is to critically discuss the principles that allow the profession of sworn translator to be practised in Poland. The rules of conducting the written examination for a sworn translator were evaluated. The assessment is based, among other things, on errors and mistakes made in the examination. In addition, the examination requirements were compared with the realities of working as a sworn translator, and proposals were made for further modifications of the examination. The analysis is based on the examination of sworn German translator.